Beyond 'Go and bring your husband': a COM-B guided qualitative study on the barriers to male involvement in antenatal care in Bamenda Health District, Cameroon. - Lily Haritu Foglabenchi; Tanya Marchant; Heidi Stöckl (PLOS Global Public Health)
Maternal and infant mortality remains a major public health concern in sub-Saharan Africa. While male involvement in pregnancy and child birth has proven to be an effective intervention that can significantly reduce these deaths, low-income settings like Cameroon continue to encounter obstacles in engaging men in maternal and child health services. This study seeks to examine and contextualize barriers to male partner involvement in antenatal care in order to inform the development of an intervention aimed at promoting male participation in maternal and child health in Cameroon. We employed a qualitative approach drawing upon 68 semi-structured interviews (SSIs) and three focus group discussions (FGDs). This involved purposively selected pregnant women (SSIs-38; FGD-01), male partners (SSIs-30; FGD-01) and health workers (FGD-01). Semi-structured interviews and group discussions were audio-recorded, transcribed and organized using Nvivo. Guided by the Capability, Opportunity and Motivation (COM-B) model of behaviour and Theoretical Domains Framework, we coded and analyzed data using directed content analysis, followed by inductive thematic analysis. Our findings suggest that, the behaviour of expectant fathers during pregnancy is shaped by the dynamic interaction between limited awareness on the role of men in pregnancy care and limited maternal agency to initiate or involve their partners in antenatal care. We also noted that the low motivation of male partners to participate in antenatal care is at the intersection of limiting health system approaches that have not moved beyond mandating women to go and bring their husbands, restrictive gender norms on masculinity-underpinned by the perception that antenatal care is a woman's affair and the fear of judgement/HIV testing. Based on our findings, we recommend that health system approaches specifically take into account existing knowledge gaps on male partner role, culture-specific gender norms and restructure the health system to promote male participation in maternal and child health services.